Study on hydrogen embrittlement susceptibility of pipeline steel under stress - Cuiwei LIU; Lanqi ZHAO; Rui ZHANG; Shiyao PENG; Rongtian LI; Xinyu XU; Yuxing LI (You-qi chuyun)
ObjectiveHydrogen embrittlement poses a significant safety risk that restricts the safe operation of hydrogen pipelines. However, there is ongoing debate regarding the extent to which hydrogen penetrates pipeline steel and induces hydrogen embrittlement under service conditions. While numerous studies indicate a substantial loss of plasticity and toughness in steel within a hydrogen environment, many hydrogen pipelines show no evident hydrogen embrittlement hazards after long-term operation. The extreme service conditions experienced by specimens during hydrogen embrittlement testing may explain the discrepancies between laboratory findings and practical engineering experiences. Therefore, it is essential to investigate how the hydrogen embrittlement testing process affects the susceptibility of materials to hydrogen embrittlement. MethodsThe mechanical properties and hydrogen embrittlement of X52 steel specimens under different hydrogen charging methods were studied by high-pressure gas-phase in-situ tensile testing under stress, with a focus on the slow strain rate tensile test. The source of hydrogen inside the specimens was explored, and then the influence of the testing process under different elastic stresses on the susceptibility of the specimens to hydrogen embrittlement was analyzed. ResultsStress is a critical factor influencing hydrogen content in the specimen and its susceptibility to hydrogen embrittlement. Consequently, the critical hydrogen concentration that leads to hydrogen embrittlement in X52 steel was determined through stressed hydrogen charging tests. The results indicated that most of the hydrogen effect originated from hydrogen penetration into the specimens under tensile conditions, with minimal penetration during the hydrogen pre-charging stage and sufficient penetration occurring during the elastic stage. ConclusionThe hydrogen-induced hardening effect occurred during the yield stage of specimens subjected to direct tensile testing in a hydrogen environment without hydrogen pre-charging, indicating that hydrogen penetrated the steel during the brief elastic stage. With stressed hydrogen charging, the hydrogen content in the specimens significantly increased. The mechanisms leading to the stress-promoted hydrogen effect include stress-enhanced hydrogen surface adsorption and internal hydrogen solubility in the gas-phase hydrogen environment. Future studies should consider the impact of slow strain rate tensile testing on hydrogen effects in materials.